A real-world pharmacovigilance analysis of hepatitis B vaccine using the U.S. Vaccine Adverse Event Reporting System (VAERS) database - Zhou, Huting; Yang, Jiale; Zhang, Jinbo; Liu, Pengcheng; Yao, Dongning (Scientific reports, 2025)
Hepatitis B vaccines (HBVs) are widely used duo to their high clinical use and mild effects. However, as post-marketing data accumulate, several serious adverse events (SAEs) following HBV have been reported. Currently, quantitative studies based on real-world data are lacking, and information on their adverse events is limited. Adverse reaction signals of the HBV were mined and analyzed using the U.S. Vaccine Adverse Event Reporting System (VAERS) to provide a reference for the safe clinical use of this vaccine. Multiple statistical methods, including the reporting odds ratio (ROR) method, the Medicines and Healthcare Products Regulatory Agency (MHRA) method, and the Bayesian Confidence Propagation Neural Network (BCPNN) method, were utilized to identify signals of HBV-associated adverse reactions, and positive signals consistent with designated medical events (DMEs) were singled out for focused comparison and discussion. Analysis of 54,136 HBV-related adverse events (AEs) identified 254 positive signals across 22 System Organ Classifications (SOCs), with General disorders and administration site conditions being the most common. Three potential positive new signals consistent with Preferred Terms (PTs) were identified in DME: Aplastic anaemia, Dermatitis exfoliative, and Haemolytic anaemia. This study suggests that HBV has a potential risk in terms of causing Aplastic anaemia, Dermatitis exfoliative, and Haemolytic anaemia. Some subtypes of Aplastic anaemia, Dermatitis exfoliative, Haemolytic anaemia are autoimmune diseases, and immunization may stimulate potential autoimmune genetic predisposition, people with autoimmune diseases or a family history of hereditary immune diseases should be monitored after receiving HBV. Health professionals should be contacted to take measures to help if anaemia, palpitations, and high fever occur.